2002
DOI: 10.1002/app.11002
|View full text |Cite
|
Sign up to set email alerts
|

Oxazoline‐containing compatibilizers for polyamide/SAN and polyamide/ABS blends

Abstract: Polyamide (PA) and acrylonitrile/butadiene/styrene copolymer (ABS) may appear as a mixture in the recycled plastic stream. The incompatibility of these blends results in a blend with poor mechanical properties. The aim of this work is to partially convert the nitrile groups of the acrylonitrile/styrene copolymer (SAN) into oxazoline groups by reaction with aminoethanol (AE). Such modified SAN (SAN-m) can react with the amine or carboxylic acid end groups of PA, and therefore used as compatibilizers for blends … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 58 publications
0
13
0
1
Order By: Relevance
“…18 In literature, an optimum amount of compatibilizer, which can provide fine and well-dispersed blend morphology, was studied and the researchers found out that after saturation concentration of compatibilizer is exceeded, the impact properties either decreased or remained constant. 6,7,22,44 In the current study, the compatibilizers used can act as tougheners because of their elastomeric nature with low glass transition temperature. For a given PA6 content, the impact strength of the blends compatibilized with EnBACO-MAH gives higher toughness than EMA-GMA due to the finer morphologies obtained in the case of EnBACO-MAH at 5 and 10% loadings.…”
Section: Mechanical Propertiesmentioning
confidence: 99%
“…18 In literature, an optimum amount of compatibilizer, which can provide fine and well-dispersed blend morphology, was studied and the researchers found out that after saturation concentration of compatibilizer is exceeded, the impact properties either decreased or remained constant. 6,7,22,44 In the current study, the compatibilizers used can act as tougheners because of their elastomeric nature with low glass transition temperature. For a given PA6 content, the impact strength of the blends compatibilized with EnBACO-MAH gives higher toughness than EMA-GMA due to the finer morphologies obtained in the case of EnBACO-MAH at 5 and 10% loadings.…”
Section: Mechanical Propertiesmentioning
confidence: 99%
“…Blends of polyamides with polyolefins and polyesters are particularly interesting and attractive from an industrial point of view. During the last years, it has been shown that such blends can be efficiently compatibilized with numerous compounds derived from maleic anhydride, acrylic acid, glycidyl methacrylate, oxazoline, etc., grafted onto the polyolefin chain so that hydrogen bonds, or even covalent bonds, can be formed between the two polymers at the blending stage [10][11][12][13][14][15][16][17][18]. Nanocomposites based on polyethylene (PE) and polyamide (PA) blends have also been studied.…”
Section: Introductionmentioning
confidence: 99%
“…The blend components covered various polymers, among which styrenic copolymers, such as acrylonitrile-butadiene-styrene (ABS), acrylonitrilestyrene (SAN) and hydrogenated styrene-butadiene-styrene (SEBS) have been widely investigated. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] However, due to thermodynamical immiscibility, polyamide-containing blends usually exhibit poor phase dispersion and interfacial adhesion, which in turn result in unsatisfactory mechanical properties. Therefore, there is extensive interest in improving their compatibility by the use of a reactive compatibilizer, to enhance the interfacial adhesion and control the morphology of the polymer blends during melt blending.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, there is extensive interest in improving their compatibility by the use of a reactive compatibilizer, to enhance the interfacial adhesion and control the morphology of the polymer blends during melt blending. [6][7][8][9][10][11][12][13][14][15][16][17][18] An effective strategy for compatibilizing immiscible blends is using in situ formed block or graft copolymers at the interface, which act as emulsifiers to stabilize the morphology formed and enhance the interfacial adhesion strength between the phases. [1,6,[14][15][16][17][18][19][20][21][22] Summary: In this work, blends of monomer casting polyamide 6 (MCPA6) and acrylonitrile-butadiene-styrene (ABS) were successfully prepared by in situ polymerization via the application of e-caprolactam as a reactive solvent.…”
Section: Introductionmentioning
confidence: 99%